Privatized corrections: questions of legality - Eisen, Lauren-Brooke (Criminology & public policy, 2019)
In this article, I look at some of the statutory and case law that has shaped the evolving regulation of the private prison industry. I also examine some critical gaps in legal issues regarding private contractors that manage prisons, jails, and detention facilities. The privatization of justice encompasses all for‐profit firms that make money in the prison‐industrial complex. Critical unanswered legal questions run the gamut from whether it is legal for corporations to pay undocumented detainees to work inside detention centers to whether it is legal for a private probation company to extend a probationer's supervision.